Simulating interactions of microrobots designed for pollutant removal in wastewater caused by the textile industry (2021)
In this work we successfully made the design and magnetic simulations of forces of a microrobot with the structure of a gripper, done for the removal of contaminants from wastewaters generated by the textile industry. This microgripper works by closing itself and capturing contaminants. We made two types of studies, the first one is a Multiphysics simulation using COMSOL Multiphysics, on this software we analyzed the behavior of the magnetic field, the magnetic flux density and the magnetization. In addition, we developed an Analytical study using MATLAB. In this study we analyzed the magnetic forces that are present on the system such as repelling and attracting forces and the magnetic torque. With the results produced we analyzed the potential interactions of the microrobots and described the magnetic behavior. We successfully described by simulations and analytically the feasibility of the physical implementation